Kant's Better-than-Terrible Argument in the Anticipations of Perception. Issue 1 (March 2020) - Landy, David
Abstract: Scholars working on Kant's Anticipations of Perception generally attribute to him an argument that invalidly infers that objects have degrees of intensive magnitude from the premise that sensations do. I argue that this rests on an incorrect disambiguation of Kant's use of Empfindung (sensation) as referring to the mental states that are our sensings, rather than the objects that are thereby sensed. Kant's real argument runs as follows. The difference between a representation of an empty region of space and/or time and a representation of that same region as occupied by an object entails that, in addition to their extensive magnitude, objects must be represented as having a matter variable in intensive magnitude. Since it is the presence of sensation (sensing) in a cognition that marks the difference between representing only the extensive magnitude of the object and the object as a whole, it is sensation that represents its intensive magnitude.